Zebras in the Forest: the experiences of Dual-Trained Child Psychiatrists and Paediatricians in Australia and New Zealand. (December 2016) - Thabrew, Hiran
Objectives: The objectives of this study were to examine the experiences of dual-trained child psychiatrists and paediatricians in Australia and New Zealand and inform the review of the Dual Fellowship Training Programme by the Royal Australian and New Zealand College of Psychiatrists and Royal Australasian College of Physicians. Methods: All dual-trained child psychiatrists and paediatricians and current trainees were electronically surveyed in 2015. Results: Seven out of eight specialists (88%) and four out of six trainees (67%) responded. Six (55%) completed or were undertaking training as part of the Dual Fellowship Training Programme. Most respondents entered dual training without difficulty, found the transition from paediatrics to adult psychiatry challenging, and were reassured by their decision to undertake dual training on reaching advanced training in child psychiatry. Benefits and downsides of dual training were noted during and following training. A significant proportion of specialists (55%) were working in hospital-based environments, especially consult liaison services, suggesting that they added long-term value to both the fields of child psychiatry and paediatrics. Conclusions: The Dual Fellowship Training Programme remains a valuable vehicle for gaining skills in paediatrics and child psychiatry. There is support for its continuation by previous and current participants.